A heterometallic [Mn9Ni2] cluster consisting of the [M4(μ3-O)3(μ3-Cl)]n+ cubane and [MnIII3(μ3-O)4]+ "V-shaped" sub-units appearing in the giant [Mn84] and [Mn70] compounds and its [Mn9CoIII2] analogue. (1st February 2022) - Moushi, Eleni E.; Charalambous, Maria; Papatriantafyllopoulou, Constantina; Christou, George; Tasiopoulos, Anastasios J.
Graphical abstract: Two analogous heterometallic [Mn IV 2 Mn III 7 Ni II 2 ] and [Mn IV 2 Mn III 7 Co III 2 ] carboxylate clusters are reported based on cubane and [Mn III 3 (μ3 -Ο)4 ] + V-shaped sub-units that have appeared in the giant [Mn84 ] and [Mn70 ] torus clusters. Magnetism studies of the [Mn IV 2 Mn III 7 Ni II 2 ] analogue revealed the presence of out-of-phase ac signals possibly due to slow relaxation of the magnetization and a Ueff value ≈ 15 K. Abstract: Two new heterometallic clusters exhibiting related cores, [Mn9 Ni2 (μ3 -Ο)10 (μ3 -Cl)2 (O2 CMe)11 (py)4 (H2 O)4 ]·2H2 O (1 ·2H2 O) (py = pyridine) and [Mn9 Co2 (μ3 -Ο)10 (μ3 -ΟΗ)2 (O2 CEt)10 (EtOH)3 (H2 O)(py)5 ](ClO4 )2 Cl (2 ) are reported. Compounds 1 ·2H2 O/2 were prepared from reactions of [Mn3 O(O2 CMe)6 (py)3 ]·py/[Mn3 O(O2 CEt)6 (py)3 ](ClO4 ) with MCl2 ·6H2 O (M = Ni 2+, Co 2+ ) and (Bu n 4 N)MnO4 in a 1:3:0.1/1:1:0.1 molar ratio in MeCN (15 ml)/MeOH-EtOH (15–0.5 ml) in ∼ 28 %/< 2 % yields, respectively. Their cores consist of two [Mn IV Mn III 2 M n + (μ3 -Ο)3 (μ3 -X)] m+ cubanes (M n + = Ni 2+, X  = Cl −, m = 5+, 1 ·2H2 O; M n + = Co 3+, X  = OH −, m = 6+, 2 ) at the terminal positions linked through a central [Mn III 3 (μ3 -Ο)4 ] + slightly V-shaped sub-unit. Interestingly, this core has appeared as a fragment in the giant [Mn84 ] and [Mn70 ] torus–like single–molecule magnets (SMMs). Magnetism studies of 1 ·2H2 O revealed the presence of competing ferromagnetic and antiferromagnetic exchange interactions leading to a fairly low spin ground state value of ST ≈ 4 or 3 and fully visible out-of-phase ac signals (above 1.8 K) indicative of slow relaxation of the magnetization and SMM behavior.